Effect pf Integrated Nutrient Management on Growth and Yield of Potato (Solanum tuberosum L.) - Saud, Ganesh; Bhattarai, Basant Raj; Mahara, Birendra (Journal of Agriculture and Resource Management, 2024)
To study the effect of integrated nutrient management on the growth and yield attributes of potatoes, this field experiment was carried out at Mangalsen Municipality, Thatikhand, Achham district, Nepal from February 2023 to June 2023. The experiment used a single-factor Randomized Complete Block Design (RCBD) with three replications and seven treatments. Different types of organic and inorganic fertilizers and their combination were used as treatment which are; T1: (RDF @ 100:100: 60), T2: (RDF @ 75% + FYM @ 20 ton/ha), T3: (RDF @ 75% + Vermicompost @ 8 ton/ha), T4: (RDF @ 75% + FYM @ 2ton/ha + Sulphur @ 20kg/ha), T5: (RDF @ 75% + FYM @ 2 ton/ha + Zincsulphate @ 20kg/ha), T6: (RDF @ 75% + FYM @ 2 ton/ha + Sulphur @ 20kg/ha + Zincsulphate @ 20kg/ha) and T7: (Control). The variety of potatoes used for research was “Khumal Seto” as it is recommended for cultivation in the high-hill and mid-hill regions of Nepal. A significant difference in plant germination, plant height, leaf number, stem number, canopy diameter, and yield attributing characters such as total number of tuber per hill, average weight of tuber, and total yield was observed among the treatments under observation. The yield parameters such as total number of tuber per hill (8.33), weight per tuber (0.08 gm), marketable tuber yield (10.24 Kg), and total yield (28.33 mt/ha), and growth parameters such as plant germination (21), plant height (39.2 cm), number of leaves (29.2), number of stems (14.26), and plant canopy (69.06) were observed highest in treatment (RDF @ 75% + FYM @ 2 ton/ha + Sulphur @ 20kg/ha + Zincsulphate @ 20kg/ha) at 75 DAS and lowest of these were measured at 45DAS in treatment Control. Therefore, Treatment RDF@ 75% + FYM @ 2ton/ ha + Sulphur@ 20kg/ha + Zincsulphate @ 20kg/ha) is best for farmers in Achham to improve the growth and yield of potatoes.